2022
DOI: 10.3390/mps5040059
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Fluid from Slaughtered Animals: A Standardized Procedure for Sampling, Storage and Use in Digestibility Trials

Abstract: Digestibility trials need a viable rumen fluid as inoculum to degrade feeds. The variability of rumen fluid depends on the animal’s diet, while its viability is greatly influenced by the sampling and handling procedures. In this article, we present a replicable protocol for sampling the rumen fluid from slaughtered animals for in vitro digestibility trials. A detailed list of the tools and a step-by-step standardized procedure for the collection, storage and the transportation of the rumen fluid from the slaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The source of rumen fluid and replication of the in vivo conditions in in vitro fermentation are the key components to overcome the challenging steps involved in in vitro rumen fermentation. The source of rumen fluid can be from live animals fed production [24] or maintenance rations [7], rumen fluid from slaughterhouses [25], or frozen rumen fluid [26,27]. Henderson et al [28] reported that the core microbiome in vivo is conserved across geographical regions no matter the species or feed; however, the relative abundances of the microbes vary with the diet and the ruminant species.…”
Section: Discussionmentioning
confidence: 99%
“…The source of rumen fluid and replication of the in vivo conditions in in vitro fermentation are the key components to overcome the challenging steps involved in in vitro rumen fermentation. The source of rumen fluid can be from live animals fed production [24] or maintenance rations [7], rumen fluid from slaughterhouses [25], or frozen rumen fluid [26,27]. Henderson et al [28] reported that the core microbiome in vivo is conserved across geographical regions no matter the species or feed; however, the relative abundances of the microbes vary with the diet and the ruminant species.…”
Section: Discussionmentioning
confidence: 99%
“…The slaughter of the animals was carried out following the animal welfare regulations. The rumen contents were collected considering the standardized procedure for sampling, storage, and use of ruminal contents recommended by Fortina et al [ 21 ]. All required consent for the procurement of fluid from slaughtered animals for research purposes was obtained from the slaughterhouse.…”
Section: Methodsmentioning
confidence: 99%
“…In lieu of ruminally fistulated animals, several authors have proposed collecting rumen fluid from recently harvested animals to obtain inoculum ( Chaudhry, 2008 ; Tassone et al, 2014 ; Sarnataro and Spanghero, 2020 ; Garcia et al, 2021 ; Fortina et al, 2022 ). Chaudhry (2008) was among the first to propose the use of fluid from recently harvested animals and found that DM disappearance was within reasonable limits but cautioned that the pre-harvest feeding regime played a significant role in the viability of the inoculum.…”
Section: Yr Later: What Progress Has Been Made Since 1993?mentioning
confidence: 99%
“… Chaudhry (2008) was among the first to propose the use of fluid from recently harvested animals and found that DM disappearance was within reasonable limits but cautioned that the pre-harvest feeding regime played a significant role in the viability of the inoculum. Fortina et al (2022) attempted to standardize the procedure for obtaining inoculum from harvested cattle and found that fluid could be stored for up to 300 min so long as anaerobic conditions and temperature were controlled.…”
Section: Yr Later: What Progress Has Been Made Since 1993?mentioning
confidence: 99%